2008
DOI: 10.1186/ar2404
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the incidence of malignancy in adult patients with rheumatoid arthritis

Abstract: Introduction The risk of malignancies in patients with rheumatoid arthritis (RA) has raised some concern, particularly with immunosuppressive approaches to disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
311
6
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(358 citation statements)
references
References 28 publications
26
311
6
15
Order By: Relevance
“…Rezultati su pokazali da je jedini važan faktor rizika za peptički ulkus kod bolesnika koji su uzimali NSAIL bila infekcija sa Helicobacter pylori (stepen vjerovatnoće 3,10; 95% CI 1,30-7,30), dok dispepsija, muški pol, godine starosti i anemija, prema rezultatima ovog istraživanja, nisu bili značajni faktori rizika. Zaključeno je da upotreba NSAIL povećava rizik od peptičkog ulkusa 3-5 puta u bolesnika sa Helicobacter pylori pozitivnim, ali i sa Helicobacter pylori negativnim testom [22][23][24][25][26].…”
Section: Diskusijaunclassified
See 1 more Smart Citation
“…Rezultati su pokazali da je jedini važan faktor rizika za peptički ulkus kod bolesnika koji su uzimali NSAIL bila infekcija sa Helicobacter pylori (stepen vjerovatnoće 3,10; 95% CI 1,30-7,30), dok dispepsija, muški pol, godine starosti i anemija, prema rezultatima ovog istraživanja, nisu bili značajni faktori rizika. Zaključeno je da upotreba NSAIL povećava rizik od peptičkog ulkusa 3-5 puta u bolesnika sa Helicobacter pylori pozitivnim, ali i sa Helicobacter pylori negativnim testom [22][23][24][25][26].…”
Section: Diskusijaunclassified
“…Ovi nalazi su bili nezavisni od starosti, pola i statusa pušenja. Potrošnja oralnih kortikosteroida se smanjila za 50%, dok je stopa imunizacije oboljelih od RA protiv gripa poboljšana za 86%, a protiv pneumokoka do 65% [24][25][26][27][28][29][30].…”
Section: Diskusijaunclassified
“…82 When compared with the general population, the standardized incidence ratio (SIR) estimates suggested that patients with RA had a twofold increase in lymphoma risk (SIR 2.08; 95% CI 1.80-2.39) and a greater risk of Hodgkin than non-Hodgkin lymphoma. The risk of lung cancer was also increased (SIR 1.63; 95% CI 1.43-1.87).…”
Section: Malignanciesmentioning
confidence: 99%
“…[82][83][84][85][86][87][88] Population studies for data collection from primary sources are required to widen the knowledge on the mechanisms of malignancy occurrence in patients with RA.…”
Section: Malignanciesmentioning
confidence: 99%
“…Patients with RA may have an increased risk of infection and some organ-specific malignancies 1,2 . Therefore, it is particularly important to monitor the incidence of infections and malignancies together with other adverse events (AE) in patients with RA treated with immunomodulatory agents.…”
mentioning
confidence: 99%